Analysis of Training Needs in the Integration of Digital Technology in Learning for Java Language Teachers - Varary Mechwafanitiara Cantika; Asep Herry Hernawan (IJECA (International Journal of Education and Curriculum Application), 2024)
Training can increase the competency of Javanese teachers regarding integrating digital technology into learning so that they no longer focus on traditional media such as textbooks. This research aims to identify prioritized training needs for Javanese language teachers in integrating digital technology into learning. Survey methods and quantitative approaches are the methods and approaches used in this research. The research population was Javanese language teachers at the Senior High School (SMA) level in East Java Province. The sample in this study consisted of 30 Javanese language teachers who were taken using an accidental sampling technique. A questionnaire is a data collection tool as well as a research instrument. The questionnaire was prepared using a Likert scale with 18 statement items. Research data were analyzed using descriptive statistics to show tendencies toward data centralization and measures of data diversity. The research results show that most teachers often participate in training activities but not training related to integrating digital technology into learning. According to the needs analysis survey, Javanese teachers need training in using online learning platforms, creating digital content, integrating digital tools in learning, and project-based learning with digital technology. This research has implications for being used as initial data for analyzing the need to develop a training curriculum for integrating digital technology in learning for Javanese language teachers.